Smart technologies and innovation for a sustainable future : proceedings of the 1st American University in the Emirates International Research Conference -- Dubai, UAE 2017 /: proceedings of the 1st American University in the Emirates International Research Conference -- Dubai, UAE 2017. ([2019]) - Unknown
No abstract available